Strategic Management of Madrasah Heads in Improving the Performance of Aliyah Teachers in Tangerang Regency - Muallim Mukhtar; Sutaryat Trisnamansyah; Yosal Iriantara; Supyan Sauri (International Journal of Science Education and Technology Management, 2022)
Education is basically an effort to help the development of children and youth to achieve certain goals that take place in a certain environment. This research is to know and analyze the Strategic Management of Madrasah Heads in Improving the Performance of Aliyah Teachers in Tangerang Regency. Data collection techniques used are observation techniques (observations), interview techniques, documentation studies, literature studies and participation. Regarding data analysis techniques using non-statistical analysis techniques. The conclusion is that the principal's management strategy in improving the performance of Aliyah teachers at MA, Tangerang Regency, through the stages of planning, implementation and evaluation is not optimal because there are still weaknesses in competence and professionalism as well as support for the fostered madrasah.